Branding Strategies as a Tool for Competitive Growth in Local Pharmaceuticals: Strategi Branding sebagai Alat untuk Pertumbuhan Kompetitif di Industri Farmasi Lokal - Khasanov Sokhib Latifovich (Academia Open, 2025)
General Background: The pharmaceutical industry plays a pivotal role in national healthcare and economic security, especially under increasing global competition and consumer demand. Specific Background: In Uzbekistan, recent state reforms have driven growth in the local pharmaceutical sector, yet many enterprises lack strategic branding, limiting their market competitiveness. Knowledge Gap: Despite global recognition of branding’s impact, local studies inadequately address its strategic, psychological, and institutional dimensions, often reducing it to superficial elements like logos or product names. Aims: This study aims to analyze the role of branding strategies in shaping a competitive environment among Uzbek pharmaceutical enterprises and to propose context-specific solutions for brand development. Results: The analysis reveals that domestic products occupy 37% of the market by volume but only 13% by value, highlighting a branding deficit. Strategic branding can enhance consumer trust, differentiate products, and increase export readiness. Novelty: The study integrates multidisciplinary branding theories with local market analysis, offering practical, evidence-based branding recommendations tailored to Uzbekistan’s pharmaceutical sector. Implications: Effective branding strategies can serve as tools for sustainable competitiveness, transforming local pharmaceutical brands into assets that foster customer loyalty, attract investment, and bolster national economic resilience.Highlights: Strategic Branding Is EssentialBranding is not just logos—it builds consumer trust, emotional connection, and long-term market positioning for local pharmaceutical firms. Local Brands Are UnderdevelopedDespite making up 37% of consumption, most Uzbek pharmaceutical companies lack a full branding platform and remain focused only on product names and packaging. Branding Boosts Export and InvestmentA strong brand image increases not just domestic loyalty but also international market access and investor appeal. Keywords: Branding Strategy, Pharmaceutical Industry, Competitive Advantage, Consumer Trust, Uzbekistan